Effect of Free Cash Flow, Enterprise Risk Management Disclosure and Sustainability Report on Company Value With Corporate Governance as Moderating Variable - Nur Aeni Waly; Noer Sasongko; Fatchan Achyani (SENTRALISASI, 2021)
This study aims to analyze the effect of free cash flow, enterprise risk management disclosure, and sustainability report on the value of companies with good corporate governance as a moderating variable listed on the Jakarta Islamic Index companies during the 2015-2019 periods. The samples used were 57 companies in (JII) period 2015 – 2019. The data analysis method used is multiple regressions with the help of Spss 26 to analyze the moderating effect. The results of this analysis show that free cash flow has no effect on firm value, enterprise risk management disclosure does not affect firm value, sustainability report does not has an effect on firm value, and good corporate governance does not moderate the relationship between free cash flow and firm value, good corporate governance moderates the relationship between enterprise risk management disclosure on firm value, and good corporate governance does not affect firm value. moderation of the relationship between the sustainability report and the value of the company.